Inactivation of fungal spores in water using ozone: Kinetics, influencing factors and mechanisms. (15th October 2020) - Wen, Gang; Liang, Zhiting; Xu, Xiangqian; Cao, Ruihua; Wan, Qiqi; Ji, Gang; Lin, Wei; Wang, Jingyi; Yang, Jingjing; Huang, Tinglin
Highlights: l Ozonation of fungal spores included two stages with different rate constants. l Increase in temperature and pH accelerated the ozonation of fungal spores. l Ozone destroyed cell wall and membrane, then released the intracellular compounds. l Ozone was more effective than chlorine and chlorine dioxide in inactivating fungi. Abstract: Fungal contamination of drinking water sources is increasingly threatening the environment and human health. In this study, the inactivation of three genera of dominant fungi in drinking water sources using ozone was first reported. The inactivation of the fungal spores by ozone could be divided into two distinct stages: first a rapid reduction in survival, and then the inactivation at a slower rate. The secondary stage inactivation fitted the Chick–Watson model well, and there was no significant difference in the second-order inactivation rate constants of the three fungal spores (0.199–0.209 L mg −1 min −1 ). The inactivation rate constants of fungal spores by molecular ozone were much lower than those of viruses, which were equivalent to that of Cryptosporidium . The increase in pH and temperature showed a positive effect on the inactivation rate. Damage to cell membranes, leakage of intracellular compounds, and changes of reactive oxygen species and esterase activity in the spores were detected after inactivation. The results indicated that ozone inactivated fungal spores by firstly destroying cell walls and membranes and then causing the release of intracellular compounds. The fungicidal efficiency of ozone was superior to those of chlorine and chlorine dioxide. In addition, the inactivation efficiency of ozone on fungal spores in real water matrices was reduced to 50.7–91.2% of the efficiency in phosphate buffer. In conclusion, ozone showed high efficiency in the inactivation of fungal spores and could be used as an alternative disinfectant for fungal contamination in drinking water sources. Graphical abstract: Image, graphical abstract